In Vitro Inhibition Capacity in Ca Oxalate Formation by Lemon (Citrus Lemon) Juice - Endang Tri Wahyuni Maharani; Jatmiko Susilo; Arifiani Agustin Amalia (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2015)
This research aims to determine the inhibition capacity of lemon juice (Citrus lemon) in the formation of calcium oxalate in a variety of concentrations of 5%, 7.5%, 10% which is then compared to pure citric acid. Lemon juice contains citric acid that can inhibit calcium oxalate’s formation. Inhibitory activity found in lemon juice is examined by observing its inhibition capacity towards the formation of calcium oxalate crystal. At the end of the treatment process the turbidity level is compared to citric acid acting as an inhibitor in the formation of calcium oxalate and then the percentage of the inhibition capacity is calculated. Result of the study shows that the optimum concentration of the lemon juice (Citrus lemon) and citric acid is 10%. The inhibition capacities in calcium oxalate formation by lemon juice with concentration variations of 5%, 7.5%, 10% are 47.06%, 73.68%, 94.19% and by citric acid with concentration variations of 5%, 7.5 %, 10% are 29.90%, 30.85%, 42.30%. It can be concluded that the higher the concentration of lemon juice and citric acid used the higher the inhibition capacity of calcium oxalate. Based on the inhibition capacity percentage, lemon juice is more effective in inhibiting the formation of calcium oxalate compared to citric acid and it can function as an alternative to prevent the formation of kidney stone. © 2015 JNSMR UIN Walisongo. All rights reserved